Concurrent application of blinatumomab and haploidentical donor leukocyte infusions for refractory primary mediastinal large B-cell lymphoma. (February 2021) - Smith, Jasmine; Kumar, Abhijeet; Stanton, Natalie A.; Katsanis, Emmanuel
Primary mediastinal large B-cell lymphoma (PMBCL) is a rare hematologic malignancy with distinct clinical and immunopathological features. We report a case of a young male with disease refractory to multiple lines of therapy, including chimeric antigen receptor-T cells, who achieved his first complete remission after haploidentical bone marrow transplantation (haplo-BMT), following donor leukocyte infusions (DLIs) given concurrently with blinatumomab. While DLI has been used after T-replete haplo-BMT with post-transplant cyclophosphamide, there are no reports on its use for PMBCL. Similarly, blinatumomab is active against B-cell lymphomas, but literature is lacking in patients with PMBCL. Our experience illustrates that blinatumomab can be used concurrently with DLI in a haploidentical setting to achieve disease response in PMBCL. Despite our encouraging experience with this case, we would not recommend this approach outside of a clinical trial as blinatumomab may exacerbate the graft versus host disease risks of DLI, especially in a haploidentical setting. Evaluating this treatment combination in high-risk patients in the setting of a clinical trial may be meaningful.